Review Of The Niet Ontvankelijk Verklaard Decision And Its Implications For The Legal Protection Of The Parties In Investment Cases (188/Pdt.G/2024/Pn Bgr) - Nanda Maghfira; Ibrahim Fajri; Annisa Aminda (Universitas Ibn Khaldun Bogor, 2026)
Investment has an important role in driving economic growth in Indonesia, as one of the main pillars of the economic system. Investment not only provides opportunities for individuals to gain financial benefits but also contributes to the creation of jobs and the improvement of people's welfare. However, stock investments do not always go according to expectations especially when mistakes or violations of the law occur that can harm shareholders. In case Number 188/Pdt.G/2024/PN Bgr, where the lawsuit was declared Niet Ontvankelijk Verklaard due to a formal defect, namely the incompatibility of the name of the attorney. This raises questions about the legal basis for the decision and its implications for the legal protection of the parties. This research aims to analyze the legal basis used by the judge in declaring the lawsuit inadmissible and its legal consequences for legal protection in investment disputes. Using a normative juridical research method with a statute approach and case approach, this research examines regulations such as Article 118 HIR, Article 1365 of the Civil Code, and court decisions. The results showed that the judge based the decision on the inconsistency of the identity of the attorney, which was considered to violate the formal requirements, so that the lawsuit was not examined for substance. As a result, the plaintiff loses access to substantive justice, creates legal uncertainty, and has the potential to reduce investor confidence, which is contrary to the principle of investor protection in Law No. 25 of 2007. This research emphasizes the need for a balance between procedural formality and substantive justice.